2021
DOI: 10.3390/agronomy11030491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Fertilizer on Bok Choy Growth and Quality in Hydroponic Cultures

Abstract: Effects of corn steep liquor (organic fertilizer, OF) and conventional chemical fertilizer (CF) on the growth and yield of bok choy (Brassica rapa var. chinensis) in summer and autumn hydroponic growing systems were compared. When OF and CF were applied with the same amount of total nitrogen in summer cultivation, there was no significant difference between yields; however, the growth rate in OF was slower than in CF. When OF was applied with twice the amount of nitrogen in CF (OF2), bok choy growth and yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Several organic fertilizers have been tested in hydroponic systems such as bonito soup, rapeseed oil cake, corn oil cake, fish meal, dried brewer's yeast, fermented tomato foliage, sea weed, and vermicaste derived solutions [5,10]. Phibunwatthanawong and Riddech [9] produced a liquid organic fertilizer for hydroponic systems from fermented molasses, distillery slop, and sugarcane leaves which had similar growth effect as chemical fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Several organic fertilizers have been tested in hydroponic systems such as bonito soup, rapeseed oil cake, corn oil cake, fish meal, dried brewer's yeast, fermented tomato foliage, sea weed, and vermicaste derived solutions [5,10]. Phibunwatthanawong and Riddech [9] produced a liquid organic fertilizer for hydroponic systems from fermented molasses, distillery slop, and sugarcane leaves which had similar growth effect as chemical fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of inorganic N recovery was systematically improved when the nutrient solution was filtrated, reinforcing the idea that undegraded organic compounds negatively impact plant growth [40]. In Kano et al's (2021) [70] study, the growth and yield of bok choy (Brassica rapa var. chinensis) under corn steep liquor organic fertilization and conventional hydroponics were similar in summer cultivation when the same amount of total N was used.…”
Section: Use Of Aerobic Degradation For Bioponic Cultivationmentioning
confidence: 83%
“…Many of these organic residues are already in a powder or liquid form and could be used in bioponics. Several studies have shown encouraging results with bioponically grown plants using corn-steep liquor and molasses [21,41,70]. Cottonseed, canola meal or corn steep liquor can represent a good source of N (4.5-7.4% DM, 5.6-6.6% DM and 3.4% DM, respectively), while molasses is reported to be a good source of K (0.5-3.8% DM) (Table 1) [21,67,68,71].…”
Section: Sources Of Organic Fertilizers For Bioponicsmentioning
confidence: 99%
“…Nilai serapan N tanaman pakcoy tertinggi terdapat pada pelakuan K3D2 dengan nilai rata-rata per tanaman sebesar 0,60 g/tanaman yang tidak berbeda nyata dengan perlakuan K2D2 dengan nilai rata-rata per tanaman sebesar 0,59 g/tanaman dan sangat berbeda nyata pada non-perlakuan atau kontrol yaitu K0D0, K1D0, K2D0, dan K3D0. Pada dasarnya tanaman menyerap nitrogen anorganik yang digunakan dalam pembentukan asam amino untuk mendukung pertumbuhan (Kano et al, 2021).…”
Section: Perlakuanunclassified